The Role of Flexible Work Arrangement on Generation Z Employee - Salsabila Ananda Putri (Publikasi Indonesia, 2025)
Changing expectations in the Generation Z workforce require organizations to revisit how to design a work system that suits the needs of flexibility, life balance, and work autonomy. Generation Z tends to value flexibility as an important role in choosing and retaining jobs, while traditional work policies are considered less relevant. This study aims to identify the role and effectiveness of Flexible Working Arrangement (FWA) on job satisfaction, productivity, and performance of Generation Z employees as well as the type of FWA that best suits the characteristics of Generation Z and what are the drivers for FWA to run effectively. The research uses a qualitative approach through the Systematic Literature Review (SLR) method with PRISMA guidance and the PICO framework to identify, screen, and synthesize relevant scientific articles. The article is included in the period 2020-2025 and obtained 10 empirical aricelles that meet the inclusion criteria for analysis. The results of the synthesis show that the implementation of FWA, such as flextime, flexplace, remote work, or hybrid, has a positive effect on job satisfaction, life balance, productivity and performance of Generation Z employees. Therefore, FWA is not only a philosophy of flexibility, but also a human resource management strategy that plays a role in improving the motivation, welfare and overall performance of Generation Z employees. This research is limited to a literature review, further research with an empirical approach is needed to verify the findings in more depth.